A two-stage Wiener filter based multi-channel feedback virtual microphone acoustic noise reducing system - PAWEŁCZYK, Marek (Archives of Acoustics, 2007)
An optimal fixed-parameter control system capable to generate zones of quiet at a number of desired locations is designed and analysed in this paper. Although it is of feedback structure the design problem is reformulated so that the Wiener filter approach can be applied. Polynomial technique is used. Due to non-minimum phase character of the plant including delays it requires performing the inner-outer factorization of a polynomial matrix and the causal-anticausal decomposition. For this control system two stages of operation can be distinguished. Experimental verification confirms that the zones of quiet are correctly distributed. Moreover, the control system remains stable for significant changes of the plant.